Uso de técnica de espectroscopia NIR no desenvolvimento de softsensor para monitoramento on-line da fermentação alcoólica industrial - Aidar Neto, Homero (Universidade Federal de São Carlos, 2024)
Automated control and monitoring of bioprocesses are fundamental tools for the modern biotechnology industry. Chemical introduction, for example, is a biotechnological process already well established in the sugar and alcohol industry, with high productivity and robust microorganisms. However, one factor can still be improved: bioprocess monito- ring. Detailed fermentation monitoring is carried out with at-line and off-line techniques, such as High Performance Liquid Chromatography (HPLC), which implies a delay to verify the end of fermentation and/or some disturb. NIR spectroscopy can be used to monitor bioprocesses, inferring key variables in fermentation in real time, such as resi- dual sugar concentration. A major difficulty in using this technique is the presence of intense noise at frequencies, requiring pre-treatment for its use in a soft sensor. The use of a phenomenological interference model can reduce the noise associated with experi- mental data, improving the estimation of interference variations using the chemometric technique. Given these aspects, a methodology was developed for inferring cell concentra- tion, substrate concentration and product concentration in a prepared fermentation. The methodology is based on smoothing experimental data from samples using a fermentative kinetic model. Such data were correlated with NIR spectra to adjust the chemometric model PLSR (Partial Least Squares Regression) and construct the virtual sensor. Three fed-batch fermentations were used to construct the detection set and three batches were used to validate the sensor.
Use of NIR spectroscopy technique in the development of a soft sensor for online monitoring of industrial alcoholic fermentation
Keywords: Fermentação alcoólica; Monitoramento; Espectroscopia NIR; Softsensor; Alcoholic fermentation; Monitoring; NIR spectroscopy; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA